Demyelination as a harbinger of lymphoma: a case report and review of primary central nervous system lymphoma preceded by multifocal sentinel demyelination. Issue 1 (December 2016) - Kvarta, Mark; Sharma, Deva; Castellani, Rudolph; Morales, Robert; Reich, Stephen; Kimball, Amy; Shin, Robert
Abstract Background Primary central nervous system lymphoma (PCNSL) may rarely be preceded by "sentinel demyelination, " a pathologic entity characterized by histologically confirmed demyelinating inflammatory brain lesions that mimic multiple sclerosis (MS) or acute disseminated encephalomyelitis (ADEM). Interpreting the overlapping radiologic and clinical characteristics associated with each of these conditions—contrast-enhancing demyelination of white matter and relapsing and remitting steroid-responsive symptoms respectively—can be a significant diagnostic challenge. Case presentation We describe a 57-year-old woman with an unusual clinical course who presented with multi-focal enhancing white matter lesions demonstrated to be inflammatory demyelination by brain biopsy. Despite a good initial response to steroids and rituximab for treatment of presumed tumefactive multiple sclerosis, the patient's condition rapidly deteriorated, and a repeat brain biopsy six months later was consistent with a diagnosis of diffuse large B-cell lymphoma. Conclusions Early clinical suspicion for PCNSL and awareness that biopsied lesions may initially show sentinel demyelination suggestive of alternate diagnoses may be essential for early initiation of appropriate therapies and mitigation of disease progression. Clinical, pathophysiological, and diagnostic aspects of sentinel demyelination and PCNSL are discussed.